Caring-based education program module for critical care nurses / Siti Aishah Ishak, Siti Khuzaimah Ahmad Sharoni and Nordianna Seman - Ishak, Siti Aishah; Ahmad Sharoni, Siti Khuzaimah; Seman, Nordianna (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Caring behavior is crucial in nursing, especially for patients with severe medical conditions admitted to hospitals. The caring-based education program module enhances nurses' caring behavior, caring efficacy, and healthy work environment. It employs the C.A.R.I.N.G acronym based on Watson’s theory of human caring. The objectives of this module are to strengthen the critical care nurses' caring behavior, caring efficacy, and work in a healthy working environment, to provide new knowledge for critical care nurses in balancing caring behavior and technology, and to enhance the quality of nursing clinical competency. The novelty of this module lies in its comprehensive integration of caring behavior into nursing education, focusing on a holistic approach, empathy, patient-centered care, theory-practice integration, and positive outcomes. The practicality of this caring-based education program module is evident in its ability to improve patient outcomes, enhance satisfaction, reduce staff burnout, promote collaboration, adapt to diverse settings, and have a lasting impact on nursing practice. This caring-based education program module serves as a vital tool to strengthen critical care nurses and other healthcare workers in delivering compassionate nursing care to patients, enhances the quality of nursing clinical competency, and satisfaction from patients and families, as a valuable guideline for future nurses, improving patient outcomes and experiences across diverse healthcare settings.